2011
DOI: 10.1007/s12185-011-0799-6
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of cancer immunoescape and development of overcoming strategies

Abstract: Cancer-induced immunosuppression is a major problem as it reduces the anti-tumor effects of immunotherapies. In cancer tissues, cancer cells, immune cells, and other stromal cells interact and create an immunosuppressive microenvironment through a variety of immunosuppressive factors. Some cancer subpopulations such as cancer cells undergoing epithelial-mesenchymal transition and cancer stem-like cells have immunosuppressive and immunoresistant properties. The production of immunosuppressive factors by cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 55 publications
1
91
0
2
Order By: Relevance
“…Fibroblasts from tumor tissues demonstrate an activated phenotype and the ability to secrete many immunosuppressive factors such as TGF, and VEGF (Yaguchi et al, 2011). Our own studies have found that undifferentiated fibroblasts, as well as MSC and CD14 + HLA-DR À monocytes, were significantly more susceptible to NK cellmediated cytotoxicity (Jewett et al, 2010); therefore, these cells may condition NK cells to undergo split anergy and become regulatory NK cells.…”
Section: Similarities In Immune Cell Effector Function In Inflammatormentioning
confidence: 99%
“…Fibroblasts from tumor tissues demonstrate an activated phenotype and the ability to secrete many immunosuppressive factors such as TGF, and VEGF (Yaguchi et al, 2011). Our own studies have found that undifferentiated fibroblasts, as well as MSC and CD14 + HLA-DR À monocytes, were significantly more susceptible to NK cellmediated cytotoxicity (Jewett et al, 2010); therefore, these cells may condition NK cells to undergo split anergy and become regulatory NK cells.…”
Section: Similarities In Immune Cell Effector Function In Inflammatormentioning
confidence: 99%
“…To enable such combinations, it is critical to determine how targeted therapies affect immune function in the tumor microenvironment and peripheral systems. Immunogenic cell death, characterized by secretion of cell damage-associated hallmark molecules consisting of calreticulin (CRT), HSP70 and 90 proteins, HMGB1, and ATP, increased expression of tumor antigens and HLA molecules, and decreased expression of immunosuppression factors are desirable features for potential immune sensitization (3,4). These effects may allow targeted agents to not only directly inhibit tumor growth, but also further enhance immune response by immunotherapy, through either tumor cell intrinsic or extrinsic immunomodulatory mechanisms, thus making the cancer therapy more effective and durable.…”
Section: Introductionmentioning
confidence: 99%
“…12,23,24 Stat3 is also a key molecule for immune suppression by stromal cells such as tumor associated macrophages (TAMs). [23][24][25] Stat3 activation in myeloid cells is significantly related to immune suppression. 26,27 We previously showed that IL-27/Stat3 signals were closely contributed to PD-L1/2 expression in TAMs.…”
Section: Discussionmentioning
confidence: 99%